Evaluation of SMEs’ Credit Decision Based on Support Vector Machine-Logistics Regression - Rui Xie; Rui Liu; Xian-Bei Liu; Jia-Ming Zhu (Journal of Mathematics)
This article uses support vector machines, logistics regression, and other methods for the comprehensive evaluation of credit decision-making of small, medium, and microenterprises and comprehensively uses software programming such as MATLAB and SPSS Modeler to solve the problem. The results, such as credit risk evaluation index system, credit risk classification model, and credit decision-making comprehensive evaluation model, are obtained. Finally, this article starts from the credit decision of small, medium, and microenterprises and provides theoretical and practical suggestions for banks to control the risks of small, medium, and microenterprises and their own development.